Legal Protection for Children Victims of Criminal Offences According to The Indonesian Juvenile Criminal Justice System - Padlah Riyadi (International Review of Social and Cultural Studies, 2025)
Children play a vital role as future national assets, yet the rise in child delinquency highlights the limitations of Indonesia's juvenile criminal justice system. Law Number 3 of 1997 emphasizes punishment (retributive justice), which often fails to rehabilitate children or support their growth. This study aims to explore policy reforms that integrate restorative justice in addressing child delinquency. Using a normative legal approach, the study analyzes secondary data through statute and conceptual frameworks. The findings suggest that restorative justice, involving victims, perpetrators, families, and communities, is more effective in resolving child delinquency while supporting rehabilitation and development. The study concludes that legal protection for children as victims in the criminal justice system requires mandatory diversion efforts by child judges, following the SPPA Law, to promote a fair and constructive resolution process.